2014
DOI: 10.1073/pnas.1417898111
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor 56 regulates mechanical overload-induced muscle hypertrophy

Abstract: Peroxisome proliferator-activated receptor gamma coactivator 1-alpha 4 (PGC-1α4) is a protein isoform derived by alternative splicing of the PGC1α mRNA and has been shown to promote muscle hypertrophy. We show here that G protein-coupled receptor 56 (GPR56) is a transcriptional target of PGC-1α4 and is induced in humans by resistance exercise. Furthermore, the anabolic effects of PGC-1α4 in cultured murine muscle cells are dependent on GPR56 signaling, because knockdown of GPR56 attenuates PGC-1α4-induced musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 27 publications
0
100
0
1
Order By: Relevance
“…Furthermore, several aGPCRs, including GPR56, are found partially uncleaved in vivo (20,36,42). For example, GPR56 in skeletal muscle was found to be almost completely uncleaved (42), although it plays critical roles in skeletal muscle cells (11,43). Together, these observations suggest that Stachel-independent mechanisms may play important roles in aGPCR signaling.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, several aGPCRs, including GPR56, are found partially uncleaved in vivo (20,36,42). For example, GPR56 in skeletal muscle was found to be almost completely uncleaved (42), although it plays critical roles in skeletal muscle cells (11,43). Together, these observations suggest that Stachel-independent mechanisms may play important roles in aGPCR signaling.…”
Section: Discussionmentioning
confidence: 89%
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%
“…A recent study has shown that coexpression of inactive Gα13 and Gα12 mutants can reverse GPR56-induced C2C12 myotube hypertrophy (50). However, the role of Gα13 in skeletal muscle had never been studied in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…The 14 kb upstream alternative Pgc-1α gene promoter is highly sensitive to stimulation, and most exercise interventions, from high-to low-intensity endurance training [57] to resistance training [36] seem to activate it to some extent. The classical proximal promoter seems to be less inducible but consistently responsive to high-intensity endurance exercise [57] or freewheel running [33,58]. Pre-treatment of exercised animals with a β-adrenergic antagonist impairs Pgc-1α-b and Pgc-1α-c induction but does not affect the induction of Pgc-1α1 [32].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%